Interpreting Legal Rights: Disparities in Judicial Treatment of Children Born Out of Wedlock in East Java, Indonesia (Lex Scientia Law Review, 2024)
The status of illegitimate children or children out of wedlock is a complex and sensitive issue that attracts attention in the Indonesian legal system. Although it has been regulated in various regulations and there is a Constitutional Court Decision Number 46/PUU-VIII/2010, implementing the protection of the legal rights of children outside marriage in different judges' decisions still experiences disparities. This article aims to analyze the differences in interpretation related to the status of children outside marriage in the judicial environment in East Java, as well as how to formulate the ideal protection of the group and civil rights of children outside marriage. This research is a non-doctrinal research using conceptual and philosophical approaches. This study found complexities in considering children's best interests in court decisions. Some judges seek to ensure the protection and rights of children born out of wedlock, while others think about social stability and religious norms. The ideal reformulation of the legal status of children born out of wedlock requires a comprehensive dialogue approach and more inclusive legal reforms. Recommendations are also made to strengthen more explicit legal guidelines for judges in dealing with such cases, considering the child's legal, religious, and best interests. This research contributes to efforts to realize ideal legal protection for out-of-wedlock children and anticipate evolving legal problems.